Switching ferromagnetic spins by an ultrafast laser pulse: Emergence of giant optical spin-orbit torque. (7th October 2016) - Zhang, G. P.; Bai, Y. H.; George, Thomas F.
Abstract: Faster magnetic recording technology is indispensable to massive data storage and big data sciences. All-optical spin switching offers a possible solution, but at present it is limited to a handful of expensive and complex rare-earth ferrimagnets. The spin switching in more abundant ferromagnets may significantly expand the scope of all-optical spin switching. Here by studying 40000 ferromagnetic spins, we show that it is the optical spin-orbit torque that determines the course of spin switching in both ferromagnets and ferrimagnets. Spin switching occurs only if the effective spin angular momentum of each constituent in an alloy exceeds a critical value. Because of the strong exchange coupling, the spin switches much faster in ferromagnets than weakly coupled ferrimagnets. This establishes a paradigm for all-optical spin switching. The resultant magnetic field (65 T) is so big that it will significantly reduce high current in spintronics, thus representing the beginning of photospintronics.